TRADISI LITERASI ISLAM DAN BUDAYA BACA MASYARAKAT ACEH - Imran Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Aceh is one area that implements Islamic law which is built on a strong foundation of literacy both memorized and written. Literacy is the capital of faith, a person can live well and truly supported by good and true literacy as well. Building a culture of literacy requires individual self-awareness, such as getting used to reading books, magazines, newspapers or other sources of information which are rare items in this technological era. The discussion about Islam as a representation of the literacy culture movement is that Islam has provided the initial foundation in the development of literacy culture,